(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: ?-Thalassemia occurs in higher frequency in the Mediterranean area and the Middle East. Classically serum ferritin and liver biopsy have been needed to monitor patient’s response to chelation therapy. Magnetic resonance imaging (MRI) has been proved effective in detecting and quantifying iron in the heart and liver. Objective:To assess the value of MRI T2* procedure in assessment of hepatic (LIC) serum ferritin level and MRI T2* of liver and myocardium in patients with BTM. Methods: A cross -sectional study was conducted at Al-Imamein Al-Kadhimein Medical City in Baghdad, from September 2016 to September 2017, 45 patients with BTM were collected from the Thalassemia center in Ibn AL-Baldy Hospital. Hepatic and myocardial T2* MRI results were taken from the file records of the patients from the same center.The results of hepatitis B and C and serum ferritin were taken from the file records. Results: The total number of patients was 60, 15 patients were excluded because of heart failure and hepatitis B and C, the mean age was (19.95±6.85 years), male: female ratio equal to 1:1. Fifty-one patients (85%) were on Deferasirox and 19 patients (31.76%) were splenectomized. Serum ferritin ranged between (1009-10600 ng/l). Liver T2* MRI ranged from (0.5-17 ms) with a mean of (3.66±3.13 ms). Mild-moderate severity found in the majority, 18 cases (40%), 13 cases (28.9%) respectively, with strong inverse correlation between liver MRI and serum ferritin level. Myocardial T2* MRI ranged from (1.88-33.2 ms) with a mean of (13.16±7.81 ms). Moderate-severe degree of severity in the majority, 12 cases (26.67%), 19 cases (42.22%) respectively, with significant inverse correlation between serum ferritin and myocardial MRI. There is no positive correlation between myocardial T2* MRI nor liver T2* MRI with mean age of the patients. Conclusion: The study shows that MRI is an accurate and non-invasive method to assess iron overload in liver and heart in ?-thalassemia patients with regular transfusion. Keywords: ?-Thalassemia major, blood transfusion, serum ferritin, cardiac MRI, hepatic MRI Citation: Yaseen AK, Abbas SS, Abdulhadi AMA. Correlation between cardiac and hepatic T2* MRI and serum ferritin level in patients with transfusion dependent ?-thalassemia major. Iraqi JMS. 2019; 17(1): 66-73. doi: 10.22578/IJMS.17.1.10